Explore Alteration of Lung and Gut Microbiota in a Murine Model of OVA-Induced Asthma Treated by CpG Oligodeoxynucleotides - Wang Q; Ji J; Xiao S; Wang J; Yan X; Fang L (Journal of Inflammation Research)
Qingqing Wang, Jingjing Ji, Shuaijun Xiao, Jiong Wang, Xuebo Yan, Lei Fang Department of Geriatric Respiratory and Critical Care, The First Affiliated Hospital of Anhui Medical University, Anhui Geriatric Institute, Hefei, Anhui, People’s Republic of ChinaCorrespondence: Jiong Wang, Email wangjiong7286@163.comAim: We sought to investigate the impact of CpG oligodeoxynucleotides (CpG-ODN) administration on the lung and gut microbiota in asthmatic mice, specifically focusing on changes in composition, diversity, and abundance, and to elucidate the microbial mechanisms underlying the therapeutic effects of CpG-ODN and identify potential beneficial bacteria indicative of its efficacy.Methods: HE staining were used to analyze inflammation in lung, colon and small intestine tissues. High-throughput sequencing technology targeting 16S rRNA was employed to analyze the composition, diversity, and correlation of microbiome in the lung, colon and small intestine of control, model and CpG-ODN administration groups.Results: (1) Histopathologically, both lung and intestinal tissue in asthmatic mice exhibited significant structural damage and inflammatory response, whereas the structure of both lung and intestinal tissue approached normal levels, accompanied by a notable improvement in the inflammatory response after CpG-ODN treatment. (2) In the specific microbiota composition analysis, bacterial dysbiosis observed in the asthmatic mice, accompanied by enrichment of Proteobacteria found to cause lung and intestinal epithelial damage and inflammatory reaction. After CpG-ODN administration, bacterial dysbiosis was improved, and a notable enrichment of beneficial bacteria, indicating a novel microecology. Meanwhile Oscillospira and Clostridium were identified as two biomarkers of the CpG-ODN treatment. (3) Heatmap analysis revealed significant correlations among lung, small intestine, and colon microbiota.Conclusion: CpG-ODN treatment can ameliorate OVA-induced asthma in mice. One side, preserving the structural integrity of the lung and intestine, safeguarding the mucosal physical barrier, the other side, improving the dysbiosis of lung and gut microbiota in asthmatic mice. Beneficial bacteria and metabolites take up microecological advantages, regulate immune cells and participate in the mucosal immune response to protect the immune barrier. Meanwhile, Oscillospira and Clostridium as biomarkers for CpG-ODN treatment, has reference significance for exploring precise Fecal microbiota transplantation treatment for asthma.Keywords: microbiota, lung-gut axis, CpG Oligodeoxynucleotides, 16S ribosomal RNA, asthma